Reviltasilsasi Pasar Tradisional Melalui Kebijakan Pemerintah Daerah: Membangun Ekonomi Lokal yang Berdaya Saing di Kota Bandar Lampung - Ali Abdul Wakhid; Abd. Qohar; Liky Faizal; Gesit Yudha; Wakhid, Ali Abdul; Qohar, Abdul Qohar; Faisal, Liky Faisal; Yudha, Gesit Yudha (Universitas Islam Negeri Raden Intan Lampung, 2025)
Traditional markets in Bandar Lampung face a decline in competitiveness due to structural, managerial, and regulatory weaknesses, especially in the face of modern retail’s rapid growth. This study aims to analyze the revitalization strategy of traditional markets through the implementation of Bandar Lampung Mayor Regulation Number 23 of 2021 and its effectiveness in supporting a competitive local economy. Employing a qualitative field research method, data were collected through interviews with key informants from the Trade Office, market traders, and community members and supported by policy documents, including national and local trade regulations. The findings reveal that revitalization efforts have not been optimal due to the limited scope of physical improvements and lack of legal enforcement. The research highlights the need for a holistic revitalization approach that integrates legal, economic, and sociological perspectives, strengthens regulatory frameworks, and empowers small traders. The study concludes that local government policies must go beyond physical infrastructure upgrades by ensuring legal certainty, participatory planning, and sustainable empowerment strategies to maintain the relevance of traditional markets in the modern economic landscape.